POLA SPASIAL PETERNAKAN AYAM DI NAGARI MUNGKA KABUPATEN LIMA PULUH KOTA - Sari, Windi Aprelia; Nefilinda, Nefilinda (Jurnal Spasial, 2024)
This research is motivated by the distribution pattern of chicken farming in Nagari Mungka. The aim of this study is to understand the distribution pattern of chicken farming in Nagari Mungka. This research is quantitative in nature. The types of data used are primary and secondary data. Data collection techniques include observation, questionnaires, and documentation. The data analysis techniques employed are Nearest Neighbour Analysis and descriptive analysis. The results of the study on the distribution pattern of chicken farming using the Nearest Neighbour Ratio indicate a value of 0.677623, which suggests a clustered distribution.